Aktualisasi Catur Wi Berlandaskan Nilai Agama Hindu Pada Joged Bungbung di Kabupaten Gianyar - Prayitna Dewi, Ida Ayu Gede; Dedi Diana, Komang; Wiwin Astari, Luh Putu (Jurnal Penelitian Agama Hindu, 2025)
Globalization seems to have had a significant influence on Joged Bungbung, where art that initially displayed an aesthetic side is now turning towards an erotic side. Like Balinese dances in general, every dance generally has a standard called catur wi or four dance element guidelines, namely wirama, wiraga, wirupa and wirasa. This wi chess certainly contains Hindu religious values. Based on Hindu religious values, the art of Joged Bungbung should remain in the aesthetic corridor. The basic problem is that there has been no in-depth study regarding the elements of catur wi which contain Hindu religious values ​​in the Joged Bungbung dance. The aim of this research is to become a reference in the development of the Joged Bungbung dance which is in accordance with Hindu religious values. Using a qualitative research methodology approach, researchers collected data, reduced data and presented data in descriptive form. Data collection was carried out using interviews, observations and document studies regarding the urgency and implementation of chess wi which is based on Hindu religious values ​​in Gianyar district. The results of this research show the urgency of actualizing chess wi based on Hindu religious values, namely, the existence of ethics and aesthetics in the art of Joged Bungbung, secondly the role of Joged Bungbung art in social life, thirdly, joged art is a dancer's self-representation. The form of actualization of chess wi which is based on Hindu religious values ​​contains religious values ​​in the components of wiraga, wirama, wirasa and wirupa. The conclusion is that Gianyar still exists and maintains the art of jogging by adhering to the tenets of chess wi which are based on Hindu religious values.